Reinventing Westminster Abbey 1642-1660: a house of kings from revolution to restoration - Merritt, J.F. (Cambridge University Press, 2016)
While historians are familiar with the destruction wrought on the nation's cathedrals during the Civil War, the rather different fate experienced by Westminster Abbey--an important symbolic building that tied together royal and religious authority--has been strangely neglected. This article argues that the Abbey played an important and distinctive role in the religious and cultural politics of the nation during the 1640s and 1650s. It uncovers the Abbey’s role in helping to legitimise successive non-monarchical regimes and ultimately explains how efforts to ‘reclaim’ the Abbey at the Restoration formed part of broader efforts to renegotiate and reinterpret the nation’s past.